2016
DOI: 10.1021/acs.organomet.6b00377
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate is DFT for Iridium-Mediated Chemistry?

Abstract: Iridium chemistry is versatile and widespread, with superior performance for reaction types such as enantioselective hydrogenation and C−H activation. In order to gain insight into the mechanistic details of such systems, density functional theory (DFT) studies are often employed. But how accurate is DFT for modeling iridium-mediated transformations in solution? We have evaluated how well DFT reproduces the energies and reactivities of 11 iridium-mediated transformations, which were carefully chosen to corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 71 publications
1
83
0
Order By: Relevance
“…M06 [54]) [26,28,30,39,43,50], but it can be noted that two studies concluded that dispersion corrections gave results that are in disagreement with experiment [22,45]. This is not in line with the general experience in the field, which shows that dispersion corrections provide more accurate reaction energies [55]. We suggest that if agreement with experiment is poor, it may point to that the mechanism occurs in a different manner than what was computed.…”
Section: Trendsmentioning
confidence: 87%
“…M06 [54]) [26,28,30,39,43,50], but it can be noted that two studies concluded that dispersion corrections gave results that are in disagreement with experiment [22,45]. This is not in line with the general experience in the field, which shows that dispersion corrections provide more accurate reaction energies [55]. We suggest that if agreement with experiment is poor, it may point to that the mechanism occurs in a different manner than what was computed.…”
Section: Trendsmentioning
confidence: 87%
“…Several criteria were applied (see below) to select the structures that were optimised in vacuo by using a DFT method that performs particularly well with transition‐metal complexes, that is, the dispersion‐corrected PBE‐D3(BJ) GGA functional . It is important to state here that control calculations carried out with the hybrid PBE0 functional gave results consistent with those produced by the latter GGA functional.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical calculations in this work have been performed using density functional theory (DFT) method, with the PBE functional in a combination with LACVP relativistic basis set with two polarization functions, as implemented in the Jaguar program package. The PBE functional has been shown to be suitable for high‐quality description of the kinetics and thermodynamics of organometallic reactions including the C−H activation . Full geometry optimization has been performed without constraints on symmetry for the gas phase.…”
Section: Methodsmentioning
confidence: 99%
“…The PBE functional has been shown to be suitable for high-quality description of the kinetics and thermodynamics of organometallic reactions including the CÀH activation. [29] Full geometry optimization has been performed without constraints on symmetry for the gas phase. Solvation energies in 2,2,2-trifluoroethol as a solvent were found using single point calculations and a Poisson-Boltzmann continuum solvation model (PBF).…”
Section: Dft Calculationsmentioning
confidence: 99%